Introduction to 3D modeling and animation - Chandramouli, Magesh (Boca Raton CRC Press, 2022)
"Graphics, 3D modeling, and animation are the cornerstones of not only the video game industry, but also the motion picture industry, digital lighting, and many other professions. Each of these subjects (Graphics, 3D modeling, and animation) intertwine with each other and even require a sufficient understanding of mathematics and physics. While other books assume readers know these basics, '3D Modeling & Animation: A Primer' provides the fundamental building blocks in constructing new own worlds of art and 3D design. With over a hundred images, valuable review questions, and coherent instructions, Magesh Chandramouli provides the reader with an essential text in the journey to mastering Graphics and 3D modeling/animation. Animation and modeling are highly stimulating subject areas, and should not watered down by pure theory and erudite equations. Without being too generic and too detailed, the book presents to you the right amount of material to provide a firm grasp of the underlying principles. The author has not explained the concepts in a simple manner, but also presented these simplified concepts in a manner that would be engaging. Key features : Provides the reader with clear, concise, instructions that help build on the fundamentals of graphics, 3D modeling, and animation. With nearly two hundred, vibrant images to help the reader understand the designing process. Review questions at the end of each chapter that will help readers hone their understanding of the content. Author Bio: Magesh Chandramouli is a Professor of Computer Graphics Technology at Purdue University Northwest. He is currently serving as the Director of Programs of the Engineering Design Graphics Division of the American Society of Engineering Education. He was a Frederick Andrews Fellow at Purdue University, West Lafayette, where he completed his doctoral studies from the Department of Computer Graphics Technology. He received Master of Science degree from the University of Calgary, Master of Engineering from the National University of Singapore, and B.E. from the College of Engineering, Guindy, India. He has received National and International Awards for his scholarly accomplishments and his work has been published and presented in reputed journals and conferences"--
Includes bibliographical references and index.
Keywords: Computer animation; Computer graphics; Three-dimensional display systems